Fundoplication in Pediatric Achalasia Patients Undergoing Heller’s Myotomy: A Systematic Review - Sarah Susanto; Brendan O’Connor; Warwick J. Teague (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Achalasia is a rare motility disorder, with the incidence being the lowest among children. The disease is caused by the inability of the LOS to relax and the absence of normal peristalsis of esophagus. Heller’s myotomy has been known to be the gold standard management of achalasia, however, reports on postoperative GERD were established in the past. To control the reflux symptoms, fundoplication has been used as an addition to Heller’s myotomy. Unfortunately, there has been an inconclusive finding from available studies regarding the need for performing fundoplication. Hence, we aim to determine whether or not the addition of fundoplication to Heller myotomy in achalasia children resulted in better postoperative outcomes and fewer complications of GERD. Methods: A literature search was carried out in four databases: Medline, EMBASE, Pubmed, and Cochrane Library. The search was limited to publications from 2006 to 2019, English studies, and achalasia patients age 0-18 years old that underwent Heller’s myotomy. The exclusion of studies from the primary screening according to title and abstracts and secondary screening on the full text were done according to a priori protocol. Duplicate studies were also eliminated by using reference management software and manually. Results: A total of 446 studies were retrieved from the search. Preliminary screening based on the eligibility criteria resulted in 21 articles to be included in this review. A total of 410 patients were included in this study, in which 80 underwent HM alone and 330 experienced fundoplication as an adjunct to HM (HMF). There was a higher proportion of asymptomatic patients in the HM group (56.3%) compared to HMF (48.8%). Both groups had a similar rate of complications (HMF 12.1%, HM 10.0%). However, in terms of postoperative GERD, slightly better results were seen among HMF patients (9.7%) than HM (15%). Conclusion: Fundoplication did not result in better resolution of symptoms, as seen from its percentage of asymptomatic patients. Improvements in postoperative GERD were seen in HMF patients, however, it was deemed as insignificant. The findings suggest that there was a limited benefit in using fundoplication.